Biomechanical, neuro-muscular and methodical aspects of running speed development - Coh, M.; Babic, V.; Mackala, K. (Journal of Human Kinetics, 2010)
The purpose of present review article is to gather the most important findings in the field of speed development including biomechanical, motor and neuro-muscular factors. Maximum speed is a complex motor ability, which manifests itself in real sports situations and is an important factor in various sports disciplines. Efficiency of maximum running is defined with frequency and the length of stride. Both variables are mutually dependant; they also depend on the processes of central regulation of motor stereotype. From the biomechanical point of view, a running stride as a basic structural unit depends on eccentric-concentric muscular cycle of take-off action. Utilisation of elastic strength in muscular-tendon complex and pre-activation of the gastrocnemius muscle is highly important in this element. Maximum running is very limited hereditary motor ability with characteristic of reduced possibility for controlling movement. Cerebellum, co-activation of muscles in kinetic chain and the frequency of activation of motor units play important roles in controlling the activation of agonists and antagonists. The prime goal of training is to create an optimal model of motor stereotype in the zone of maximum speed. Such process has to be long term and methodical.